GUIDELINES FOR NEW PUBLIC MANAGEMENT IN ACCORDANCE WITH GOOD GOVERNANCE PRINCIPLES OF PHETCHABURI MUNICIPALITY, PHETCHABURI PROVINCE - Yoddokmai, Lanchakon; Maitreesophon, Bampen (Journal of Graduate School Sakon Nakhon Rajabhat University, 2024)
This mixed-method research aimed to 1) examine the level of New Public Management of Phetchaburi Municipality, 2) compare respondents’ opinions on New Public Management, 3) explore good governance principles that affected New Public Management, and 4) establish guidelines for New Public Management in accordance with good governance principles. The sample groups were 170 personnel and 8 key informants from Phetchaburi Municipality. Data were analyzed using percentage, mean, standard deviation, t-test, One-Way ANOVA, multiple regression, and content analysis. The findings were as follows: 1) The New Public Management of Phetchaburi Municipality was rated at a high level, 2) Different personal characteristics showed no differences in opinions regarding New Public Management, 3)Decentralization and equity aspects affected New Public Management at the 0.001 level of significance, while the consensus-oriented aspect influenced it at the 0.05 level of significance, and 4) The guidelines for new public management in accordance with good governance principles recommend that individual organizations should effectively delegate jobs and responsibilities, enhance personnel development, prioritize service quality, work effectively and accurately to attain goals, incorporate private sector administration and management practices, and utilize resources with maximum profits.